The Bible and crusade narrative in the twelfth century - Smith, Katherine Allen (The Boydell Press, 2020)
A new investigation into the twelfth-century accounts of the First Crusasde, showing their complex relationship with the Bible
Title from publisher's bibliographic system (viewed on 30 Apr 2020)
Keywords: Bibel; Crusades / Historiography; Crusades / Biblical teaching; Rezeption; Bibelwissenschaft; Bibellektüre; Kreuzzug -- 1096-1099; Geschichtsschreibung